2013
DOI: 10.13102/sociobiology.v60i1.35-40
|View full text |Cite
|
Sign up to set email alerts
|

Fumigant Activity of Eight Plant Essential Oils Against Workers of Red Imported Fire Ant, Solenopsis invicta

Abstract: Plant essential oils from eight plant species were tested for their insecticidal activities against the red imported fire ant, Solenopsis invcita, by using a fumigation bioassay. This study reveals that the mortalities after treatment of the workers of red imported fire ants varied according to the classification of workers, oil type, dosage, and exposure time. Among the essential oils tested, strong insecticidal activity was observed with the essential oils of camphor (Cinnamomum camphora), artemisia annua (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 13 publications
1
19
1
Order By: Relevance
“…Essential oil from mint oil and wintergreen are also reported as being toxic to fire ants (Appel et al, 2004;Tang et al, 2013). Bioactive compounds from Tephrosia vogelii Hook.…”
Section: Research Article -Antsmentioning
confidence: 99%
See 2 more Smart Citations
“…Essential oil from mint oil and wintergreen are also reported as being toxic to fire ants (Appel et al, 2004;Tang et al, 2013). Bioactive compounds from Tephrosia vogelii Hook.…”
Section: Research Article -Antsmentioning
confidence: 99%
“…and Artemisia argyi H. Lév. and Vaniot are also reported as repellents against fire ants (Wang et al, 2012;Tang et al, 2013;Wang et al, 2014).…”
Section: Research Article -Antsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the toxicity of botanical essential oils on red imported fire ant have shown that various essential oils are repellent and/or toxic to the ant (Tang et al, 2013). Mint oil granules were proven to be toxic and repellent to red imported fire ants (Appel et al, 2004).…”
mentioning
confidence: 99%
“…Mint oil granules were proven to be toxic and repellent to red imported fire ants (Appel et al, 2004). The essential oils of camphor, Artemisia annua, eucalyptus, mugwort, turpentine wintergreen, chrysanthemum, and forsythia showed effective fumigation toxicity against the red imported fire ant (Tang et al, 2013). In a previous study on the anti-termitic activity of essential oils and their chemical constituents, 5 mg/g each of benzaldehyde, R-terpineol, neral, geraniol, eugenol, cinnamyl alcohol, and cinnamaldehyde exhibit 100% mortality after 1 d post-treatment (Chang & Cheng, 2002).…”
mentioning
confidence: 99%